Mathematics for Elementary School Teachers - Bassarear, Tom (Cengage Learning, Inc, 2005)
Mathematics for Elementary School Teachers, 3/e, offers pre-service teachers a comprehensive mathematics course designed to foster concept development through examples, investigations, and explorations. Visual icons throughout the main text allow instructors to easily connect the text to the hands-on activities in the corresponding Explorations Manual